Ethics issues identified by applicants and ethics experts in Horizon 2020 grant proposals [version 2; peer review: 2 approved] - Ivan Buljan; David G Pina; Ana Marušić (F1000Research, 2021)
Background: We assessed the ethics review of proposals selected for funding under the Marie Skłodowska-Curie Actions (MSCA) and the European Research Council (ERC) in Horizon 2020, EU’s framework programme for research and innovation, 2014-2020. Methods: We analysed anonymized datasets for 3,054 MSCA individual fellowships (IF), 417 MSCA Innovative Training Networks (ITN), and 1,465 ERC main-listed proposals with ethics conditional clearance, over four years (2016 to 2019). The datasets included the information on ethics issues identified by applicants in their proposal and ethics issues and requirements identified by ethics experts during the ethics review. Results: 42% of proposals received ethical clearance. For proposals with conditional ethics clearance (n=3546), most of the identified ethics issues by both applicants and ethics experts were in the ethics categories related to humans; protection of personal data; environment, health and safety; and non-EU countries. Ethics experts identified twice as many ethics issues compared to applicants across funding schemes, years, and from high- and low-research performing countries. ERC grants had the highest number of ethics requirements per proposal (median (Md)=8, interquartile range (IQR=4-14), compared to ITN (Md=6, IQR=3-13) and IF grants (Md=3, IQR=2-6). The majority of requirements had to be fulfilled after grant agreement: 99.4% for IF, 99.5% for ITN, and 26.0% for ERC. For 9% of the proposals, the requirements included the appointment of an independent ethics advisor and 1% of the proposals had to appoint an ethics advisory board. Conclusions: Many applicants for highly competitive H2020 funding schemes lack awareness of ethics issues raised by their proposed research. There is a need for better training of researchers at all career stages about ethics issues in research, more support to researchers from research organizations to follow the funding agencies requirements, as well as further development and harmonization of the ethics appraisal process during grant assessment.